The role of salmonid fishes in conservation of the endangered freshwater pearl mussel (Margaritifera margaritifera) - Salonen, Jouni (Aquatic Conservation: Marine and Freshwater Ecosystems, 2016)
The abundance of freshwater pearl mussels (Margaritifera margaritifera) has declined widely during the past century, and new conservation initiatives are needed. This thesis focused on the relationship between M. margaritifera and its salmonid host required for reproduction of this species. First, by exposing fish experimentally to glochidium larvae of M. margaritifera, different M. margaritifera populations were shown to demonstrate strong differences in their ability to parasitize different salmonid species. Atlantic salmon was clearly a better host for mussels in large river channels, whereas in small headwater tributaries brown trout was the best, or the only suitable, host. These findings provide a previously unrecognised explanation for the collapse and the lack of recruitment especially of the salmon-specific M. margaritifera populations; a high proportion of large salmon rivers were dammed for hydropower production in the 1960s, which prevented the migration of salmon and thus left M. margaritifera without the appropriate host in these rivers. Furthermore, an invasive salmonid, brook trout, was widely introduced to small tributaries above the dams in the past, but in this study was shown to be an unsuitable host for M. margaritifera. Thus, and due to the tendency of brook trout to replace native brown trout, the spread of brook trout is an additional threat to M. margaritifera. An indication of local adaptation of M. margaritifera, i.e. higher infectivity in sympatric salmonid host strain than in allopatric populations of the same species, was also detected. Finally, a new, non- destructive approach to search for M. margaritifera populations, involving electrofishing and quick visual examination of the gills of captured salmonids, revealed the occurrence of 3 previously unknown populations. The results of this thesis highlight the importance of taking into account the roles of salmonid fish in future efforts to search, protect and restore freshwater pearl mussel populations.